Innovacionnye technologii v sporte i fiziceskom vospitanii - Rodionov, V. A.; Kozlova, S. Ju. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2016)
The article presents a comparative analysis of published materials of scientific-practical conferences of 2013 and 2016 years. Conferences, which are held regularly at Pedagogical Institute of Physical Culture and Sports of MCU, reflect trends the development of innovative technologies in sports and physical education.